Penerapan Teknologi Augmented Reality Dengan Metode Marker Based Tracking Untuk Media Promosi Objek Wisata Kabupaten Aceh Singkil Berbasis Android - Syamsuwardin Syamsuwardin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Aceh Singkil is one of the districts in Aceh Province. As one of the regencies that has beautiful tourism objects, Aceh Singkil Regency prioritizes the tourism sector as one of its regional income. Promotions that are used to introduce existing tourism objects in the district of Aceh Singkil through conventional print media such as the usual brochures without involving increasingly developing technology are currently considered less attractive. Conventional promotional media such as brochures require innovation so that they are more interesting, by combining augmented reality technology to introduce tourism objects in the district of Aceh Singkil. Attractions introduced in the form of 3D and based on Android. Based on the above problems will be solved by providing innovation to the promotional media used such as brochures using the Augmented reality Marker Based Tracking method. That is expected to be more interesting and increase tourist visits to attractions in the district of Aceh Singkil.